Pengembangan Perangkat Pembelajaran Model Problem Based Instruction (PBI) Terhadap Hasil Belajar Siswa dan Kemampuan Menulis Laporan Ilmiah : Learning Media Development of Problem Based Instruction Method Toward Student Outcome and The Skill’s of Writing Scientific Report - Medyata Rika Niki; Elsje Theodora Maasawet; Susilo Susilo (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2019)
Learning Media Development of Problem Based Instruction Method Toward Student Outcome and The Skill’s of Writing Scientific Report Teachers can develop learning tools according to their needs in Biology lessons. This study aims to determine the results of needs analysis, validation analysis, usefulness to improve the ability to write reports, analysis of the effectiveness of the development of the device. This research is a development research using quantitative and qualitative methods. Previously, researchers took data analysis of teacher needs, more than 60% still did not use the device to the fullest, 75% of teachers had not yet made an assessment rubric. The learning kit was declared valid with a presentation of 89.6%. And there is an increase in the learning outcomes of students in the control and experimental classes because t-count <-table = -20.96 <-1.67 at SMA Negeri 2 Samarinda. Keywords: Learning Tools, PBI, Scientific Reports, Learning Outcomes Abstrak : Pengembangan Perangkat Pembelajaran Model Problem Based Instruction (PBI) Terhadap Hasil Belajar Dan Kemampuan Menulis Laporan Ilmiah Biologi SMAN 2 Di Samarinda. Guru dapat mengembangkan perangkat pembelajaran sesuai dengan kebutuhan dalam pelajaran Biologi. Penelitian ini bertujuan untuk mengetahui hasil analisis kebutuhan , analisis validasi, ketermanfaatan untuk meningkatkan kemampuan menulis laporan, analisis keefektifan pengembangan perangkat. Penelitian ini merupakan penelitian pengembangan menggunakan metode kuantitatif dan kualitatif. Sebelumnya peneliti mengambil data analisis kebutuhan guru, lebih dari 60 % masih belum menggunakan perangkat secara maksimal, guru 75 % belum membuat rubrik penilaian. Perangkat pembelajaran dinyatakan valid dengan presentasi 89,6 %. Dan terdapat peningkatan hasil belajar siswa kelas kontrol dan eksperimen karena thitung <-ttabel = -20,96 <-1,67 di SMA Negeri 2 Samarinda. Kata kunci : Perangkat Pembelajaran, PBI, Laporan Ilmiah, Hasil Belajar